Optimasi Efisiensi Antena Microstrip Circular Patch menggunakan Optimizer CST, Algoritma Memetika, dan Slot Rectangular pada WiFi 5 GHz - Ulima Achva, RA. Jihan; Fadhli, Mohammad (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2023)
Wireless communication is an important requirement in various applications, especially in WiFi networks. The efficiency of an antenna is a crucial aspect in designing wireless communication system and plays a significant role in ensuring strong and reliable signal transmission. This research belongs to comparison of the result of optimizing the efficiency of microstrip circular patch antennas for 5GHz WiFi frequencies using the optimizer in CST, memetic algorithm and rectangular slot. From the simulation result, the efficiency values of the microstrip circular patch antennas using different optimization methods are as follows, microstrip circular patch antenna using the optimizer in CST 63,03%, microstrip circular patch antenna using the memetic algorithm 57,23%, and microstrip circular patch with a rectangular slot 56,20%. Additionally, the total efficiency simulation result show that the total efficiency value of the microstrip circular patch antenna using optimizer at cst is 62.8%, the microstrip circular patch uses the memetic algorithm 54.68%, ang the microstrip circular patch slot rectangular antenna is 56.20%.